Donor derived leukemia in allogeneic transplantation. Issue 12 (15th October 2021) - Aldoss, Ibrahim; Clark, Mary; Marcucci, Guido; Forman, Stephen J.
Abstract: Allogeneic hematopoietic cell transplantation (alloHCT) is a curative option for the treatment of eligible patients with hematological malignancies. This modality confers a risk for life-threatening complications, including the rare and underdiagnosed complication of donor-derived leukemia (DDL). DDL differs from relapse of the original malignancy in that DDL originates from the donor stem cells and is unrelated to the original diagnosis. Because DDL may be the same lineage as the original diagnosis, it is difficult to identify these cases and many remain unrecognized. There is no consensus of how to approach the treatment of patients with DDL, and their prognosis is poor considering that patients with DDL have already been treated for their original leukemia and have undergone alloHCT. DDL occurs following transplants using any donor stem cell source (bone marrow, peripheral blood and cord blood) and any donor type (matched/unmatched, related/unrelated and haploidentical). Both donor and recipient factors contribute to the development of DDL, and a better understanding of these factors is crucial to reduce the risk for the development of DDL. In this review, we provide an overview of DDL, including the incidence, diagnosis, etiology, prognosis, and treatment.